Progress or more of the same?: electronic monitoring and parole in the age of mass incarceration - Kilgore, James (Critical criminology, 2013)
Often billed as an "alternative to incarceration", electronic monitoring (EM) is widely trumpeted as a key method of reducing incarceration costs while maintaining public safety. However, little research has been done which closely examines EM in the historical context of mass incarceration and the paradigm of punishment. This article focuses on the use of EM in parole in that broader context. Through research into the legal and policy frameworks for EM as well as via personal interviews with people who have been on EM while on parole, the author concludes that the present EM practice reinforces the dominant punishment paradigm and places major obstacles in the way of the successful re-entry for people returning from prison. He concludes with some concrete recommendations about changes in law, policy and implementation guidelines that would allow EM to operate in an environment more conducive to rehabilitation.